Workforce education for Latinos : politics, programs, and practices - Huerta-Macías, Ana (Bergin & Garvey, 2002)
This text examines political, curricular and instructional issues in workforce education, and concludes that such policies are inequitable and that they are marginalizing Latinos. She proposes changes that should provide avenues for economic and educational advancement for Latino adults.